A metakaolin-based polymer grouting material and its preparation method and application
Patent Information
- Application Number
- CN202411493148.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing grouting materials have shortcomings in compressive strength and durability, which are difficult to meet the construction needs under complex geological conditions in deep underground projects.
Using metakaolin base polymer grouting materials, by reasonably preparing metakaolin, alkaline slag, modified bentonite, nano-copper oxide modified microcrystalline cellulose, eggshell powder, gadolinium doped cerium oxide, expansion agent and exciter, A grouting material with excellent mechanical properties and adhesion is formed.
It realizes the high compressive strength, good fluidity, strong viscosity, water retention and durability of the grouting material, and is suitable for deep underground rock formation reinforcement and crack repair.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of grouting materials, and in particular to a metakaolin-based polymer grouting material and a preparation method and application thereof. Background Art
[0002] In recent years, with the utilization of energy and resources and the construction of hydropower and transportation, the types of underground projects have continued to increase and gradually expanded to deeper underground. Deep underground space usually has extremely complex geological conditions, which may cause frequent engineering disasters. For example, in the construction of underground space and underground projects, factors such as the instability and large deformation of rock formations, groundwater infiltration, ground stress changes, and fault activity not only increase the difficulty and risk of construction, but may also seriously threaten the safety of life and property of construction workers. Grouting technology injects liquid materials with solidification ability into broken surrounding rocks through pressure delivery technology, fills the cracks in the surrounding rocks, and rebonds the broken rock mass together, thereby improving the mechanical properties of the rock mass. At present, grouting reinforcement technology has been widely used to solve the problem of broken surrounding rock and bottom plate support in underground projects.
[0003] Grouting materials are one of the key factors affecting the effect of grouting reinforcement. At present, there are hundreds of grouting materials, which are mainly divided into two categories: inorganic grouting materials and organic grouting materials. Organic grouting materials have the advantages of low viscosity and good injectability, and can be injected into tiny cracks and pores, but organic grouting materials are usually toxic, pollute the environment, have poor durability, and are expensive. Inorganic grouting materials have the advantages of good injectability and low price, but their compressive strength and durability are poor.
[0004] In view of the problems existing in the existing grouting materials, developing a grouting material with good grouting effect, high compressive strength, good injectability and strong durability is a technical problem that needs to be solved urgently in this field. Summary of the invention
[0005] In view of the above problems, the present invention provides a metakaolin-based polymer grouting material and a preparation method and application thereof.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] The invention provides a metakaolin-based polymer grouting material, which is composed of the following raw materials in parts by weight: 80-150 parts of metakaolin, 20-40 parts of alkaline slag, 6-12 parts of modified bentonite, 4-8 parts of nano-copper oxide-modified microcrystalline cellulose, 5-10 parts of eggshell powder, 1-3 parts of gadolinium-doped cerium oxide, 0.5-1.5 parts of an expander, and 20-30 parts of an activator.
[0008] Furthermore, the particle size of the metakaolin is 1000-1200 meshes, the particle size of the alkaline slag is 900-1000 meshes, the particle size of the modified bentonite is 180-200 meshes, and the particle size of the eggshell powder is 300-400 meshes.
[0009] Furthermore, the preparation method of the modified bentonite is: add 5% zirconium silicate aqueous solution to bentonite, heat to 65°C for reaction for 5 hours, filter, roast the filter cake at 500°C for 3 hours, add 20% tetraethylammonium chloride aqueous solution, react at 60°C for 2 hours, filter, dry, crush and sieve to obtain.
[0010] Furthermore, the nano-copper oxide-modified microcrystalline cellulose is microcrystalline cellulose with nano-copper oxide loaded on its surface, and the mass ratio of microcrystalline cellulose to nano-copper oxide is 15:1; the preparation method of the nano-copper oxide-modified microcrystalline cellulose is as follows: dispersing the microcrystalline cellulose in a 2 mol / L ammonium persulfate solution, stirring at 65° C. for 8 h, drying, adding the solution to a nano-copper oxide-n-hexane suspension, ultrasonically treating the solution for 10 min, and vacuum drying the solution.
[0011] Furthermore, the expansion agent consists of calcium sulphoaluminate and calcium oxide in a mass ratio of 5:1.
[0012] Furthermore, the activator is composed of potassium hydroxide, sodium hydroxide and water glass in a mass ratio of 3-5:2:5.
[0013] The present invention also provides a method for preparing a metakaolin-based polymer grouting material: all raw materials are taken by weight for later use; metakaolin, alkaline slag, modified bentonite, nano-copper oxide-modified microcrystalline cellulose, eggshell powder, gadolinium-doped cerium oxide, an expander and an activator are uniformly mixed, water is added, and the mixture is uniformly stirred at a high speed to obtain the grouting material.
[0014] Furthermore, the mass ratio of the raw material to water is 1:0.3-0.5; and the stirring speed is 500-1000r / min.
[0015] The invention also provides an application of a metakaolin-based polymer grouting material, and the grouting material is applied in the fields of rock reinforcement and crack repair.
[0016] In the present invention, the metakaolin grouting material provides excellent mechanical properties and adhesion, and the alkaline slag accelerates the polymerization reaction of the metakaolin-based polymer grouting. At the same time, because the slag contains calcium oxide, it can participate in the early polymerization reaction after dissolution, promote gel formation, and improve the early strength of the material. By modifying the bentonite, the specific surface area and thixotropy of the bentonite are improved, which helps to increase the fluidity of the grouting material and facilitate grouting; in addition, the bentonite can absorb free water and improve the stability of the grouting material; it has a certain expansibility after contacting water, and can form a dense stone body, alleviate the volume shrinkage of the stone body in the later stage, prevent microcracks caused by shrinkage in the early stage, improve viscosity, water retention, impermeability, etc., and improve the grouting effect. Nano-copper oxide-modified microcrystalline cellulose can prevent cracks caused by early shrinkage and improve the compressive strength and impermeability of the grouting material. Eggshell powder has a microporous structure with high porosity and specific surface area, which is conducive to adsorbing fine particles in the microporous structure, improving its dispersion uniformity in the grouting material, and improving the compressive strength after grouting, especially the later strength. Gadolinium-doped cerium oxide as an electrolyte can improve the fluidity of the grouting material, making it easier to pour; at the same time, it can also improve the water retention of the material. The expansion agent makes the grouting material have a micro-expansion effect, which is convenient for filling pores and reducing fine cracks. The activator can effectively stimulate the material to better polymerize, form a more stable chemical bond and spatial structure, and enhance the erosion resistance and mechanical properties of the metakaolin-based polymer grouting material.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] The metakaolin-based polymer grouting material of the present invention has reasonable components, simple preparation, excellent performance, strong fluidity, high compressive strength, good water retention, good injectability and durability, excellent grouting effect, can meet the needs of reinforcing underground rock formations and filling and repairing tiny cracks and fissures, and is suitable for large-scale use in engineering. DETAILED DESCRIPTION
[0019] In order to make the purpose and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0020] The instruments, reagents, materials, etc. involved in the following examples, unless otherwise specified, are all conventional instruments, reagents, materials, etc. in the prior art and can be obtained through regular commercial channels. The experimental methods, detection methods, etc. involved in the following examples, unless otherwise specified, are all conventional experimental methods, detection methods, etc. in the prior art.
[0021] Preparation Example 1
[0022] Preparation of modified bentonite: add 5% zirconium silicate aqueous solution (mass ratio 4:1) to bentonite, heat to 65℃ for reaction for 5h, filter, calcine the filter cake at 500℃ for 3h, add 20% tetraethylammonium chloride aqueous solution, react at 60℃ for 2h, filter, dry at 150℃ for 3h, crush, and pass through a 180-200 mesh sieve to obtain.
[0023] Preparation Example 2
[0024] Preparation of nano-copper oxide-modified microcrystalline cellulose (nano-copper oxide is loaded on the surface of microcrystalline cellulose, the mass ratio of the two is 15:1, and the particle size of nano-copper oxide is 50 nm): disperse the microcrystalline cellulose in 2 mol / L ammonium persulfate solution, stir at 65°C for 8 h, dry and add to nano-copper oxide-n-hexane suspension (the mass fraction of nano-copper oxide is 5%), ultrasonically treat for 10 min, and vacuum dry to obtain the result.
[0025] Example 1
[0026] The present embodiment provides a metakaolin-based polymer grouting material, which is composed of the following raw materials in parts by weight: 80 parts of metakaolin (1000 mesh), 20 parts of alkaline slag (900 mesh), 6 parts of modified bentonite (180 mesh), 4 parts of nano-copper oxide-modified microcrystalline cellulose, 5 parts of eggshell powder (300 mesh), 1 part of gadolinium-doped cerium oxide, 0.5 parts of an expander (calcium sulfoaluminate and calcium oxide in a mass ratio of 5:1), and 20 parts of an activator (potassium hydroxide, sodium hydroxide, and water glass in a mass ratio of 3:2:5).
[0027] The preparation method of the grouting material comprises the following steps: taking all raw materials by weight for standby use; uniformly mixing metakaolin, alkaline slag, modified bentonite, nano copper oxide modified microcrystalline cellulose, eggshell powder, gadolinium doped cerium oxide, an expander and an activator, adding 0.3 times of water, and uniformly stirring at a high speed of 500 r / min to obtain the grouting material.
[0028] Example 2
[0029] The present embodiment provides a metakaolin-based polymer grouting material, which is composed of the following raw materials in parts by weight: 120 parts of metakaolin (1100 mesh), 30 parts of alkaline slag (950 mesh), 9 parts of modified bentonite (190 mesh), 6 parts of nano-copper oxide-modified microcrystalline cellulose, 8 parts of eggshell powder (350 mesh), 2 parts of gadolinium-doped cerium oxide, 1.0 part of an expander (calcium sulfoaluminate and calcium oxide in a mass ratio of 5:1), and 25 parts of an activator (potassium hydroxide, sodium hydroxide, and water glass in a mass ratio of 4:2:5).
[0030] The preparation method of the grouting material comprises the following steps: taking all raw materials by weight for standby use; uniformly mixing metakaolin, alkaline slag, modified bentonite, nano copper oxide modified microcrystalline cellulose, eggshell powder, gadolinium doped cerium oxide, an expander and an activator, adding 0.4 times of water, and uniformly stirring at a high speed of 800 r / min to obtain the grouting material.
[0031] Example 3
[0032] The present embodiment provides a metakaolin-based polymer grouting material, which is composed of the following raw materials in parts by weight: 150 parts of metakaolin (1200 mesh), 40 parts of alkaline slag (1000 mesh), 12 parts of modified bentonite (200 mesh), 8 parts of nano-copper oxide-modified microcrystalline cellulose, 10 parts of eggshell powder (400 mesh), 3 parts of gadolinium-doped cerium oxide, 1.5 parts of an expander (calcium sulfoaluminate and calcium oxide in a mass ratio of 5:1), and 30 parts of an activator (potassium hydroxide, sodium hydroxide, and water glass in a mass ratio of 5:2:5).
[0033] The preparation method of the grouting material comprises the following steps: taking all raw materials by weight for standby use; uniformly mixing metakaolin, alkaline slag, modified bentonite, nano-copper oxide-modified microcrystalline cellulose, eggshell powder, gadolinium-doped cerium oxide, an expander and an activator, adding 0.5 times of water, and uniformly stirring at a high speed of 1000 r / min to obtain the grouting material.
[0034] Comparative Example 1
[0035] The difference from Example 2 is that the metakaolin-based polymer grouting material does not contain alkaline slag, and the other raw material compositions and preparation methods remain unchanged.
[0036] Comparative Example 2
[0037] The difference from Example 2 is that the metakaolin-based polymer grouting material does not contain modified bentonite, and the other raw material compositions and preparation methods remain unchanged.
[0038] Comparative Example 3
[0039] The difference from Example 2 is that the metakaolin-based polymer grouting material does not contain nano-copper oxide-modified microcrystalline cellulose, and the other raw material compositions and preparation methods remain unchanged.
[0040] Comparative Example 4
[0041] The difference from Example 2 is that the metakaolin-based polymer grouting material does not contain eggshell powder, and the other raw material compositions and preparation methods remain unchanged.
[0042] Comparative Example 5
[0043] The difference from Example 2 is that the metakaolin-based polymer grouting material does not contain gadolinium-doped cerium oxide, and the other raw material compositions and preparation methods remain unchanged.
[0044] The metakaolin-based polymer grouting materials prepared in the above Examples 1-3 and Comparative Examples 1-5 were tested as follows:
[0045] Pour the newly mixed metakaolin-based polymer grouting material into a truncated cone mold (top inner diameter 70mm, bottom inner diameter 100mm, height 60mm), let it stand for 30 seconds, then lift the truncated cone mold vertically to allow the slurry to flow on the glass plate without any disturbance. Let it stand for 30 minutes, measure the maximum diffusion diameter of the slurry and its vertical diameter, and take the average of the two as the fluidity result.
[0046] The freshly mixed metakaolin-based polymer grouting material was poured into a 40×40×40mm plastic mold and sealed with a plastic film. After curing, it was demoulded and transferred to a standard curing box (20±2℃, 95±5%RH) for curing until the test age. Three parallel groups were set up at each age to test the compressive strength of the metakaolin-based polymer grouting material.
[0047] Pour the freshly mixed metakaolin-based polymer grouting material into a 100 mL measuring cylinder and seal the mouth of the measuring cylinder with a plastic film. After standing for 3 hours, measure the water seepage rate of the grouting material.
[0048] The above test results are shown in Table 1.
[0049] Table 1 Test results of grouting materials of Examples 1-3 and Comparative Examples 1-5
[0050]
[0051] From the results in Table 1, it can be seen that the fluidity of the metakaolin-based polymer grouting materials prepared in Examples 1-3 is all above 300 mm, the 1d compressive strength is above 16 MPa, the 7d compressive strength is above 41 MPa, the 28d compressive strength is above 50 MPa, and the water seepage rate is lower than 0.15%. It can be seen that the metakaolin-based polymer grouting materials prepared in Examples 1-3 have strong fluidity, high compressive strength, good water retention, and good injectability, which can ensure that the slurry flows smoothly into the fine cracks under the pumping of the grouting pump and fills the rock stratum cracks, has a good grouting effect, good injectability, strong durability, and is suitable for large-scale use in engineering.
[0052] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A metakaolin-based polymer grouting material, characterized in that: The invention is composed of the following raw materials in parts by weight: 80-150 parts of metakaolin, 20-40 parts of alkaline slag, 6-12 parts of modified bentonite, 4-8 parts of nano copper oxide modified microcrystalline cellulose, 5-10 parts of eggshell powder, 1-3 parts of gadolinium doped cerium oxide, 0.5-1.5 parts of expander and 20-30 parts of activator; The preparation method of the modified bentonite is as follows: add 5% zirconium silicate aqueous solution to bentonite, heat to react at 65°C for 5h, filter, roast the filter cake at 500°C for 3h, add 20% tetraethylammonium chloride aqueous solution, react at 60°C for 2h, filter, and dry to obtain the modified bentonite.
2. The metakaolin-based polymer grouting material according to claim 1, characterized in that: The particle size of the metakaolin is 1000-1200 meshes, the particle size of the alkaline slag is 900-1000 meshes, the particle size of the modified bentonite is 180-200 meshes, and the particle size of the eggshell powder is 300-400 meshes.
3. The metakaolin-based polymer grouting material according to claim 1, characterized in that: The nano-copper oxide-modified microcrystalline cellulose is microcrystalline cellulose with nano-copper oxide loaded on its surface, and the mass ratio of microcrystalline cellulose to nano-copper oxide is 15:1; the preparation method of the nano-copper oxide-modified microcrystalline cellulose is as follows: dispersing the microcrystalline cellulose in a 2 mol / L ammonium persulfate solution, stirring at 65° C. for 8 h, drying, adding the solution to a nano-copper oxide-n-hexane suspension, ultrasonically treating the solution for 10 min, and vacuum drying the solution.
4. The metakaolin-based polymer grouting material according to claim 1, characterized in that: The expansion agent is composed of calcium sulphoaluminate and calcium oxide in a mass ratio of 5:
1.
5. The metakaolin-based polymer grouting material according to claim 1, characterized in that: The activator is composed of potassium hydroxide, sodium hydroxide and water glass in a mass ratio of 3-5:2:
5.
6. A method for preparing a metakaolin-based polymer grouting material according to any one of claims 1 to 5, characterized in that: All raw materials are taken by weight for later use; after evenly mixing metakaolin, alkaline slag, modified bentonite, nano-copper oxide-modified microcrystalline cellulose, eggshell powder, gadolinium-doped cerium oxide, expansion agent and activator, water is added and stirred evenly at high speed to obtain grouting material.
7. The method for preparing a metakaolin-based polymer grouting material according to claim 6, characterized in that: The mass ratio of the raw material to water is 1:0.3-0.5; the stirring speed is 500-1000r / min.
8. An application of the metakaolin-based polymer grouting material according to any one of claims 1 to 5, characterized in that: The grouting material is used in the fields of rock reinforcement and crack repair.
Citation Information
Patent Citations
Eggshell powder modified concrete and preparation method thereof
CN111925162A
Ultra-high performance concrete with low fluidity loss and preparation method thereof
CN114956718A
High-strength plastic concrete for underground diaphragm wall
CN115724635A